Perbedaan Pengaruh Latihan Shuttle Run dan Zig-Zag Run terhadap Kelincahan Pemain Futsal di Tunas Muda Eleven - Faricha D; Syurrahmi Syurrahmi; Najizah F; Abidin Z (Lembaga Pengembangan Kinerja Dosen, 2025)
Agility is an important aspect in futsal because it plays a role in the player's ability to make quick movements and changes of direction. Two types of exercises commonly used to improve agility are shuttle runs and zig-zag runs; however, the effectiveness of each exercise has not been clearly determined. Therefore, this study was conducted to determine the difference in the effects of shuttle run and zig-zag run exercises in improving the agility of futsal players at Tunas Muda Eleven. Research Design: This study used a quasi-experimental method with a pre-test and post-test design. A total of 22 male futsal players aged 13–15 years were divided into two groups. Group 1 received shuttle run training and Group 2 received zig-zag run training for 3 weeks, 4 sessions per week, with a total of 12 training sessions. Agility was measured using the Agility T-Test before and after the intervention. Results: Both shuttle run and zig-zag run training significantly improved agility scores (p < 0.05). But Independent Sample T-Test showed no significant difference between shuttle runs and zig-zag runs (p > 0.05). Conclusion: there was no difference in the effect of the two exercises on the agility of futsal players at Club Eleven.